Bottle Neck Point Rattan Industry Cluster Development in Palu City - Asngadi Asngadi; Mas’adah Mas’adah; Sulaiman Miru; Saharuddin Kaseng (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Rattan industry has been designated as a core competency of regional industry (KIID) Palu City, which will be encouraged to become a commodity and product as a regional superior because of the availability of abundant rattan resources. Although Central Sulawesi Province is the largest supplier of rattan in Indonesia, rattan industry clusters actually grow and develop in various places outside Central Sulawesi.  The purpose of this research is specifically to identify bottleneck points for the development of the Palu City rattan industry, because the development efforts of the Palu City rattan industry have not been optimal until now.  The bottleneck point reflects the main problem that must be immediately resolved. The research paradigm is qualitative, with phenomenological analysis tools. For this reason, the researcher is the main instrument in this study. The number of key informants consisted of 9 key informants consisting of 4 business people, namely 2 rattan furniture and 2 rattan accessories, 3 government elements and 2 academics involved in rattan research. The results of this study indicate that the bottleneck point occurs in the sociohistorical aspects of product, industrialization, and sustainability   in the development of the rattan industrial cluster in Palu City.